Enacting corporate governance of healthcare safety and quality: a dramaturgy of hospital boards in England. Issue 2 (4th August 2015) - Freeman, Tim; Millar, Ross; Mannion, Russell; Davies, Huw
Abstract: The governance of patient safety is a challenging concern for all health systems. Yet, while the role of executive boards receives increased scrutiny, the area remains theoretically and methodologically underdeveloped. Specifically, we lack a detailed understanding of the performative aspects at play: what board members say and do to discharge their accountabilities for patient safety. This article draws on qualitative data from overt non‐participant observation of four NHS hospital Foundation Trust boards in England. Applying a dramaturgical framework to explore scripting, setting, staging and performance, we found important differences between case study sites in the performative dimensions of processing and interpretation of infection control data. We detail the practices associated with these differences ‐ the legitimation of current performance, the querying of data classification, and the naming and shaming of executives – to consider their implications.